2021
DOI: 10.15252/embr.202052164
|View full text |Cite
|
Sign up to set email alerts
|

CUL2LRR1, TRAIP and p97 control CMG helicase disassembly in the mammalian cell cycle

Abstract: The eukaryotic replisome is disassembled in each cell cycle, dependent upon ubiquitylation of the CMG helicase. Studies of Saccharomyces cerevisiae, Caenorhabditis elegans and Xenopus laevis have revealed surprising evolutionary diversity in the ubiquitin ligases that control CMG ubiquitylation, but regulated disassembly of the mammalian replisome has yet to be explored. Here, we describe a model system for studying the ubiquitylation and chromatin extraction of the mammalian CMG replisome, based on mouse embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(97 citation statements)
references
References 71 publications
13
84
0
Order By: Relevance
“…Together, these results suggest that deubiquitylation of MCM7 mediated by p97 and proteasomal degradation could drive the disassembly of the replicative helicase during termination. Consistent with the results for S. cerevisiae, X. laevis, C. elegans embryos and mouse embryonic stem cells [7,8,13] , we identi ed that polyubiquitylation of MCM7 plays a conserved role in regulating replisome disassembly from chromatin in humans.…”
Section: Inhibition Of Replication By Dna Damage Obviously Reduces Polyubiquitylation Of Mcm7 Mediated By Rnf8supporting
confidence: 86%
See 3 more Smart Citations
“…Together, these results suggest that deubiquitylation of MCM7 mediated by p97 and proteasomal degradation could drive the disassembly of the replicative helicase during termination. Consistent with the results for S. cerevisiae, X. laevis, C. elegans embryos and mouse embryonic stem cells [7,8,13] , we identi ed that polyubiquitylation of MCM7 plays a conserved role in regulating replisome disassembly from chromatin in humans.…”
Section: Inhibition Of Replication By Dna Damage Obviously Reduces Polyubiquitylation Of Mcm7 Mediated By Rnf8supporting
confidence: 86%
“…3A and 4F) have not been reported, which remains to be further investigated. In mouse embryonic stem cells, study found that ubiquitin ligases CUL2LRR1 and TRAIP control p97dependent replisome disassembly during DNA replication termination and mitosis, respectively [13] , which may also regulate the ubiquitination of MCM7 in Human, and is worth for further investigation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A cell entering mitosis may have under-replicated sister chromatids (URSCs) which contain loci that failed to complete replication during interphase, and these URSCs must be resolved to prevent DNA bridges during anaphase. TRAIP initiates the resolution of URSCs by ubiquitylating the MCM7 subunit of CMG helicase, thus triggering replication machinery unloading from stalled forks and allowing sister chromatid resolution via mitotic DNA repair synthesis (Deng et al, 2019; Priego Moreno et al, 2019; Sonneville et al, 2019; Villa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%